(untitled) (CIPEEX, 2025)
Obesity is a chronic global condition, affecting approximately 7 million people in Brazil, according to data from the Ministry of Health. On the other hand, according to the International Society of Aesthetic Plastic Surgery, Brazil is the second country in the world with the highest number of aesthetic procedures, performing 112,186 abdominoplasties. Given this, with the significant increase in the number of obese individuals, the demand for bariatric surgery has grown considerably, being seen as an effective alternative for weight loss and improving quality of life. However, the rapid and significant weight loss can result in undesirable effects, both physical and emotional, such as sagging skin and low self-esteem. In this context, plastic surgery, especially dermolipectomy, plays an essential role in addressing and solving these problems. Objective: To analyze the main techniques of abdominal dermolipectomy and their complications in post-bariatric patients. Methodology: This study is an integrative literature review, using studies found in the databases Scientific Electronic Library Online (Scielo) and Google Scholar, based on the DeCS/MESH terms: “bariatric surgery,” “body contouring,” and “abdominoplasty.” Boolean operators "AND" and "OR" were applied. Five articles that answered the guiding question were selected, with those that did not fit the theme or were not available in full being excluded. Results: In studies focused on post-surgical satisfaction, it is evident that there is an improvement in quality of life, greater self-acceptance, improvement in depressive symptoms, mood, and self-confidence in post-bariatric patients who underwent dermolipectomy, with abdominal surgery being the most common. However, it is worth noting that a higher number of complications were observed in bariatric patients compared to those without previous surgeries, with the complication rate in corrective surgeries post-bariatric surgery being 42%. The most frequent complications are related to wound healing, necrosis, infection, and skin dehiscence. Furthermore, in studies covering technical aspects, the most commonly used abdominal dermolipectomy techniques are: classic abdominoplasty, Scarpa’s fascia, and fleur-de-lis. Conclusion: It is concluded that abdominal dermolipectomy in patients without previous surgery presents lower complication rates when compared to procedures performed in recent post-bariatric patients. However, the wide range of abdominoplasty techniques allows for more individualized and appropriate treatment for each patient, thus reducing the chances of complications. Nonetheless, more long-term research is needed to consolidate knowledge and ensure the safety of the procedure in post-bariatric patients.